2006
DOI: 10.1002/ar.a.20309
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangiogenesis by blind‐ended vessel sprouting is concurrent with hemangiogenesis by vascular splitting

Abstract: Development of effective vascular therapies requires the understanding of all modes of vessel formation involved in angiogenesis (here termed "hemangiogenesis") and lymphangiogenesis. Two major modes of vessel morphogenesis include sprouting of a new vessel from a preexisting vessel and splitting of a preexisting parent vessel into two offspring vessels. In the quail chorioallantoic membrane (CAM) during mid-development (embryonic days E6 -E9), lymphangiogenesis progressed primarily via blind-ended vessel spro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 57 publications
(85 reference statements)
0
30
1
Order By: Relevance
“…In contrast to own and other earlier studies on CAM pericytes Hagedorn et al 2004;Nico et al 2004;Parsons-Wingerter et al 2006;Hlushchuk et al 2007), we could show here by combination with SNA ( Fig. 2a, b) that DES and SMA are present in the CAM capillary plexus, and are intimately related to its endothelial layer at least after E12 (even as early as E10, not shown).…”
Section: Desmin and Sma Expression In The Mature Camcontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to own and other earlier studies on CAM pericytes Hagedorn et al 2004;Nico et al 2004;Parsons-Wingerter et al 2006;Hlushchuk et al 2007), we could show here by combination with SNA ( Fig. 2a, b) that DES and SMA are present in the CAM capillary plexus, and are intimately related to its endothelial layer at least after E12 (even as early as E10, not shown).…”
Section: Desmin and Sma Expression In The Mature Camcontrasting
confidence: 99%
“…Moreover, yet other reports are in conXict with respect to SMA expression, which was described either as not before E12 (Hlushchuk et al 2007) or transiently early: E8 (Parsons-Wingerter et al 2006). Taken together, despite the description of "endothelial-like cells" and their extensions during IA (Patan et al 1993(Patan et al , 1996, and their more recent interpretation as pericytes or myoWbroblasts (Burri et al 2004), cytoskeletal properties and arrangement of periendothelial cells and their processes remained enigmatic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another equally important issue is the remodeling that eliminates nascent vessels during the transformation of the primitive vascular network into a mature branching vasculature. To complicate this picture of coronary vessel development, Qh-1 labels not just blood vessel precursors but distinctly labels lymphatic precursors (Parsons-Wingerter et al, 2006) in the chorioallantoic membrane (extraembryonic tissue) and we have recently found that the same is true in the developing epicardium (Karunamuni et al, 2010). Therefore, some of the structures labeled with Qh-1 and identified as nascent blood vessels may be nascent lymphatic vessels.…”
Section: Where Do Endothelial Cells In the Heart Come From?mentioning
confidence: 99%
“…Other lymphatic-gene mouse models are available, such as mice deficient for Net (93), podoplanin (94), neuropillin-2 (NRP-2) (95), angiopoietin-2 (Ang2) (96), integrin-␣ 9 (97), p85 subunit of PI3K (98) (102). The avian chorioallantoic membrane (CAM) was used to support this concept of progenitor cell recruitment and to demonstrate its dependence to VEGF-C (103,104).…”
Section: Embryonic Lymphangiogenesismentioning
confidence: 99%